Flavonoids and arbutin from Turnera diffusa - Piacente, Sonia; Camargo, Ely E. S. [UNESP]; Zampelli, Aurelia; Gracioso, Juliano S.; Souza Brito, Alba R.; Pizza, Cosimo; Vilegas, Wagner [UNESP] (My University, 2002)
The infusion of the aerial parts of Turnera diffusa was phytochemically examined. Chromatographic procedures led to the isolation of a new flavone glycoside, five known flavonoids and p-arbutin. Structures were determined by 1D- and 2D NMR experiments, as well as ES-MS and UV spectra.
Keywords: Flavonoids; Turnera diffusa; Africa; Arbutin; Magnetic Resonance Spectroscopy; Molecular Structure; North America; Plant Extracts; Plants, Medicinal; South America; Turnera